THE EFFECT OF SALES GROWTH, COMPANY SIZE, LEVERAGE ON TAX AVOIDANCE - Putri, Octa Ramadina; Rochayatun, Sulis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
This study aims to gain knowledge regarding the effect of sales growth, company size and the effect on tax avoidance practices on companies. Companies often avoid taxes in ways that are not following the law. The practice of tax avoidance is a practice carried out by companies legally following the law. Sales growth, company size, and leverage are all factors in legal tax evasion. The research method used is a quantitative approach using the financial statements of companies listed on the Indonesia Stock Exchange for 2020-2022. The research sample consists of several companies from the trading sector. The conclusion from this research is that all companies from various sectors need to study the factors of tax avoidance as an efficient tax decision-making and payment.